Effect of Parental Myopia on Change in Refraction in Shanghai Preschoolers: A 1-Year Prospective Study - Ma, Yingyan; Lin, Senlin; Zhu, Jianfeng; Zhao, Rong; Zhang, Bo; Yin, Yao; Shao, Yueqin; He, Xiangui; Xu, Xun; Zou, Haidong (Frontiers in Pediatrics, 2022)
Background: To investigate risk factors for change in refraction and refractive components in preschoolers. Methods: Preschool children aged 3 to 5 years old, from the junior and the middle grade of seven randomly selected kindergartens in Jia Ding District, Shanghai were followed for one year. Cycloplegic autorefraction (1% cyclopentolate) and axial length were measured at baseline and at 1-year follow-up. Questionnaires about parental myopia, and environmental risk factors such as time of outdoors and near work were collected. Results: A total of 603 right eyes of 603 children were included. Parental myopia was not associated with change in refraction, but two myopic parents was associated with longer change in axial length (Coefficient=0.153, P=0.006), after adjusted for baseline spherical refraction, age, gender, change in height, change in weight, and environment risk factors. In the multivariate analyses, boys showed a more myopic refraction shift than girls in the one year (Coefficient=-0.150, P=0.008), and a quicker axial length elongation (Coefficient=0.120, P=0.008). Time of near work, including watching television, using computer, reading and writing, and time of outdoor activities were not associated with change in refraction or axial length. Conclusions: In preschool age, environmental risk factors were not strongly associated with the change in refraction or refractive components. Parental myopia influence children’s refractive development continuously from infancy to preschool age, which might be the biological basis of school myopia.